REL-1017 (Esmethadone), A Novel NMDAR Blocker for the Treatment of MDD is Not Neurotoxic in Sprague-Dawley Rats - Bifari, Francesco; Pappagallo, Marco; Bleavins, Michael; Traversa, Sergio; Folli, Franco; Manfredi, Paolo L. (Frontiers in Pharmacology, 2022)
Esmethadone (REL-1017; dextromethadone) is the dextro-isomer of the racemic mixture, dextro,levo-methadone. REL-1017 acts as a low affinity, low potency N-methyl-D-aspartate receptor (NMDAR) channel blocker with rapid, robust, and sustained therapeutic effects in patients with major depressive disorder (MDD). Systemic administration of some NMDARs blockers may cause transient and reversible pathomorphological changes in brain neurons characterized by cytoplasmic vacuolization called Olney’s lesions, leading also to irreversible neuronal necrosis. Here we aimed to determine whether REL-1017 administration via oral gavage for 1 up to4 days to Sprague-Dawley (SD) rats could produce initial or cumulative neurotoxic effects or other evidence of neural damage, including cortical neurons death and microgliosis as compared with MK-801. As previously shown, NMDR channel blocker MK-801 produced severe clinical impairment, Olney’s lesions, neuronal necrosis and cortical microgliosis. Administration of REL-1017 at low (20 - 31.25; mg/kg in female-male), mid (40 - 62.5; mg/kg) or high (80-110 mg/kg) doses did not cause any transient and irreversible pathomorphological changes in brain neurons both at the retrosplenial and olfactory bulb sites. Notably, these doses of REL-1017 are around 200 to 1000 fold higher than the therapeutic dose employed in humans. The neurotoxic effect of MK801 is sexually dimorphic, since females appear to be markedly more sensitive than males. The experimental data showed the absence of neurotoxicity and no sex dimorphism of REL-1017. In conclusionREL-1017 did not produce initial or cumulative neurotoxic effects or other evidence of damage to cortical neurons, further encouraging the development of REL-1017 for the treatment of MDD and other neuropsychiatric disorders.